3D-Finite element modeling of lead rubber bearing using high damping material - Basshofi Habieb Ahmad; Tavio Tavio; Milani Gabriele; Wijaya Usman (MATEC Web of Conferences, 2019)
Lead Rubber Bearing (LRB) has been widely applied for seismic protection of mid and high-rise buildings around the world. Its excellent energy dissipation becomes the most important aspect of this isolation system thanks to the plasticity and recovery behavior of the lead core. Aiming to develop a deeper knowledge on the behavior of LRB’s, a 3D detailed finite element (FE) modeling is performed in Abaqus FE software. Some important parameters involved in the model are plasticity of the lead core and hyper-elasticity and viscosity of the rubber material. The parameters for rubber material are derived from the results of experimental works in the laboratory, including uniaxial tensile test and relaxation test. The bearing model is then subjected to a cyclic shear-test under constant vertical load. The result of the 3D-FE model is then compared with the analytic-Abaqus model for LRB isolators, developed in the literature. Finally, both 3D-FE model and analytic model result in a good agreement on the shear behaviour of the presented LRB.